Peran Pembelajaran Shorof terhadap Kemampuan Membaca Al-Qur’an Siswa Di Pondok Pesantren Darul Ilmi Yayasan Al-Husna Janji Matogu - Dani, Suci Rahma (EL-EMIR Institute, 2025)
This study aims to describe the role of shorof learning on students' Quranic reading ability. Shorof learning is a branch of Arabic language science that studies changes in word form and their influence on meaning. By understanding shorof, students are expected to more easily recognize word forms in the Quran, thereby improving their reading skills according to the rules of tajwid. This study used a qualitative method with a literature study approach and limited observations of students at an Islamic junior high school (madrasah tsanawiyah). Data were collected through classroom observations, teacher interviews, and document review. The results indicate that shorof learning significantly contributes to improving Quranic reading ability, particularly in terms of fluency, accuracy, and understanding of word structure. The conclusion of this study confirms that integrating shorof into Quranic learning is crucial as a strategy to improve students' Quranic reading competence.